2021
DOI: 10.1016/j.mjafi.2021.02.010
|View full text |Cite
|
Sign up to set email alerts
|

Reinfection in COVID-19: A scoping review

Abstract: Reinfections in COVID-19 are being reported all around the world and are a cause for concern, considering that a lot of our assumptions and modeling (including vaccination) related to the disease have relied on long-term immunity. We were one of the first groups to report a series of 4 healthcare workers to have been reinfected. This review article reports a scoping review of the available literature on reinfections, with a discussion of the implications of reinfections.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 30 publications
1
15
0
Order By: Relevance
“… 35 Previous studies, largely in the form of case reports and series, have reported different types of comorbidities, reflective of altered immune status, and positive associations with reinfection. 36 , 37 …”
Section: Discussionmentioning
confidence: 99%
“… 35 Previous studies, largely in the form of case reports and series, have reported different types of comorbidities, reflective of altered immune status, and positive associations with reinfection. 36 , 37 …”
Section: Discussionmentioning
confidence: 99%
“…Age is a factor that is widely linked to the behavior of the virus and the secondary immune response to the physiological reserve, establishing conditions of prognosis and severity. 13 , 17 Case reports published in 2020 and 2021, with study populations in Asia, Europe, North and South America, found that reinfection cases cover a varied age range, documenting patients from 4 years to over 100, with a higher frequencies between the third and fourth decades of life, but with a higher risk of complications associated with admission to the ICU or the need for mechanical ventilation after 65 years of age, 16 , 18 further increasing this condition before the presence of comorbidities, also being the age group with the highest number of deaths, although lower than what was found in the first episodes and with lower prevalence’s in younger populations 2 ; keeping a relationship with what is presented in our study.…”
Section: Discussionmentioning
confidence: 95%
“…In coronavirus cases, reinfection has been associated with short-term immunity and genetic changes in viruses which allow them to escape from immune response 2 ; these reinfections mainly occur in persons with mild disease, or asymptomatic, in which a fast decrease of antibody titers is noticed. 4 - 6 …”
Section: Introductionmentioning
confidence: 99%
“…A study in Mexico found only 258 instances of reinfection in a cohort of 100,432 participants (2.6 per 1000) [99]. Reinfection depends upon both, the level of immunity a person gains from the first infection, and the level of likely exposure due to social and working environments [100]. To exclude persistence of viral RNA, reinfection is proven only when both the first and the second infections have been sequenced and shown to be different variants of the virus [100].…”
Section: Reinfection With Sars-cov-2-when Does It Occur and How Can It Be Verified?mentioning
confidence: 99%
“…Reinfection depends upon both, the level of immunity a person gains from the first infection, and the level of likely exposure due to social and working environments [100]. To exclude persistence of viral RNA, reinfection is proven only when both the first and the second infections have been sequenced and shown to be different variants of the virus [100]. A less rigorous way of looking for reinfection is to document a positive PCR test at a set time interval after the last known PCR or antibody test [98].…”
Section: Reinfection With Sars-cov-2-when Does It Occur and How Can It Be Verified?mentioning
confidence: 99%